Entrepreneurial Orientation and Total Quality Management as Determinants of SME Performance: Evidence from the Mediating Effect of Open Innovation - I Gusti Made Priyambhada Putra (Universitas Pendidikan Ganesha, 2025)
SME's Performance is a key indicator of business success that reflects the ability of business actors to manage resources, maintain competitiveness, and achieve business goals in a sustainable manner. However, there is still limited research that examines the integrative role of entrepreneurship orientation and quality management in improving the performance of MSMEs through open innovation mechanisms. This study aims to analyze the influence of Entrepreneurial Orientation and Total Quality Management on SME's Performance with Open Innovation as a mediation variable. This research is a quantitative research with a survey design. The research population is a barbershop MSMEs in Singaraja, Bali, with a focus on small category businesses. The research sample amounted to 85 respondents who were selected using the probability sampling technique. Data was collected through a structured questionnaire and analyzed using Structural Equation Modeling based on Partial Least Squares (PLS-SEM) with the help of the SmartPLS version 4 application. Data analysis includes measurement model tests (outer model) and structural model tests (inner model). The results of the study show that Entrepreneurial Orientation and Total Quality Management have a significant effect on SME's Performance. In addition, Open Innovation has been proven to significantly mediate the influence of Entrepreneurial Orientation and Total Quality Management on the performance of MSMEs. These findings imply the importance of strengthening entrepreneurial orientation, quality management practices, and the adoption of open innovations in improving the performance of MSMEs in a sustainable manner.